Review of Małgorzata Borowska, Maria Kalinowska, Jarosław Ławski and Katarzyna Tomaszuk, eds., Filhellenizm w Polsce: Rekonesans - Ioannidou, Alexandra (Historein, 2022)
Review of Małgorzata Borowska, Maria Kalinowska, Jarosław Ławski and Katarzyna Tomaszuk, eds., Filhellenizm w Polsce: Rekonesans. Warsaw: Wydawnictwa Uniwersytetu Warsazwskiego, 2007. 348 pp. To view the full text, click on the button "HTML".